Analysis of Structural Behavior with Stage Construction Analysis Method Compared to Conventional Analysis on Tegalalang Bali Real Estate Building - I Wayan Gunawan; Hanie Teki Tjendani; Ar. RA. Retno Hastijanti (Jurnal Teknik Indonesia, 2026)
Conventional structural analysis methods have shortcomings because they assume construction is complete, leading to overestimation in columns and walls. Deformation occurs due to self-weight, altering heights during casting, alongside creep (inelastic deformation from constant loads) and shrinkage (volume change from water loss). Thus, stage construction analysis (SCA) is essential. Analysis followed SNI requirements for shear force (V), vibration period (T), displacement (????), and stress ratio. Structural elements were grouped by construction stages and contours. In SCA, dead and additional dead loads are defined non-linearly, matching stages. SCA increases displacement/deformation by 43% (x-direction), 39% (y), and 44% (z), iron work volume by 7%, and internal forces, reducing column capacity by 27.7% on average. Differences from conventional methods arise because SCA models groups per construction stages, using Nonlinear Stage Construction Load Case for self-weight and dead loads, unlike Static Linear Load Case.